Structural alteration of a BYDV-like translation element (BTE) that attenuates p35 expression in three mild Tobacco bushy top virus isolates - Deya Wang (Nature Portfolio, 2017)
Abstract To identify the molecular effects of Tobacco bushy top virus (TBTV) evolution on the degeneration of tobacco bushy top disease, three TBTV isolates with mild virulence were compared with wild-type TBTV to assess the translation of p35, which relies on a BYDV-like translation element (BTE) in a cap-independent manner. The in vitro expression of p35 in the mild isolates was only 20% to 40% of the expression observed in wt TBTV. Based on translation data from chimeric TBTV RNA, low-level p35 expression in the three mild isolates was associated with two regions: the 5′ terminal 500 nt region (RI) and the 3′ internal region (RV), which included the BTE. For the RV region, low level p35 expression was mainly associated with structural alterations of the BTE instead of specific sequence mutations within the BTE based on SHAPE structural probing and mutation analysis. Additionally, structural alteration of the TBTV BTE resulted from mutations outside of the BTE, implying structural complexity of the local region surrounding the BTE. This study is the first report on the structural alteration of the 3′ cap-independent translation element among different isolates of a given RNA virus, which is associated with variations in viral virulence.